2019
DOI: 10.1088/1361-648x/aaf989
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of sub-nanometer metallic clusters

Abstract: At the nanoscale, the investigation of structural features becomes fundamental as we can establish relationships between cluster geometries and their physicochemical properties. The peculiarity lies in the variety of shapes often unusual and far from any geometrical and crystallographic intuition clusters can assume. In this respect, we should treat and consider nanoparticles as a new form of matter. Nanoparticle structures depend on their size, chemical composition, ordering, as well as external conditions e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 276 publications
(295 reference statements)
1
69
0
1
Order By: Relevance
“…Barriers were found to be accessible at room temperature up to Ni 561 and Cu 561 , while higher barriers were found for Pd, Pt, Au and Ag. [27][28][29] Barreteau et al found energy barriers for Pd 147 and Rh 147 to be larger than 4 eV and larger than 10 eV for Pd 309 and Rh 309 using a tight binding approach. 30 This work is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers were found to be accessible at room temperature up to Ni 561 and Cu 561 , while higher barriers were found for Pd, Pt, Au and Ag. [27][28][29] Barreteau et al found energy barriers for Pd 147 and Rh 147 to be larger than 4 eV and larger than 10 eV for Pd 309 and Rh 309 using a tight binding approach. 30 This work is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The most stable structures reported for different cluster sizes exhibit either very regular shape (e.g. Au 20 or Ag 55 ) or amorphous patterns 50 . As an example, it has been reported that Au 55 could present cavities below its outer shell 33,48,51 and a competition between ordered and disordered geometries has been evidenced in the case of Au 147 33,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the crystallization of the Au NCs structures likely occurs more easily in the gas‐phase where Au clusters are free from any gas or support interaction. [ 63 ] The dispersion of these naked clusters is preserved upon soft landing on the FTO surface. The high stability of these (quasi)crystalline structures makes them resistant to oxidation during the CV scans avoiding their deactivation by surface restructuring.…”
Section: Resultsmentioning
confidence: 99%